Indocyanine Green Laser Angiography Improves Deep Inferior Epigastric Perforator Flap Outcomes following Abdominal Suction Lipectomy. Issue 3 (March 2015) - Casey, William J.; Connolly, Katharine A.; Nanda, Alisha; Rebecca, Alanna M.; Perdikis, Galen; Smith, Anthony A.
Abstract : Background: The reliability of deep inferior epigastric artery perforator (DIEP) flap reconstruction following abdominal liposuction is controversial. The authors' early cases were technically successful; however, they experienced high partial flap loss and fat necrosis rates. The authors sought to compare DIEP flap outcomes in the setting of prior liposuction after the use of intraoperative indocyanine green angiography compared to when flaps were assessed on clinical grounds alone. Methods: A retrospective review of a consecutive series of DIEP flaps following liposuction at a single institution was performed, comparing those evaluated on clinical grounds alone and those in which indocyanine green angiography was used intraoperatively. Outcomes measured included anastomotic complications, total flap loss, partial flap loss, fat necrosis, and postoperative abdominal wounds. Results: Thirteen DIEP flaps following prior liposuction were performed on 11 patients from July of 2003 through January of 2014. All patients had preoperative imaging with duplex ultrasound or computed tomographic angiography to analyze perforator suitability before surgical exploration. Seven flaps were evaluated intraoperatively on clinical grounds alone. Six flaps were assessed and modified based on indocyanine green angiography. All flaps were successful; however, partial flap loss and fat necrosis rates dropped from 71.4 percent to 0 percent when indocyanine green angiography was used intraoperatively ( p = 0.02). Conclusions: Indocyanine green angiography is an excellent vascular imaging modality for intraoperative use to assess flap perfusion, and improves outcomes in DIEP flaps when harvested after prior abdominal suction lipectomy.